European student’s mathematical olympiad’ 09 - Dzindzalieta, Dainius (Lietuvos matematikos rinkinys, 2009)
In this article we talk about Vojtech Jarn¸ kk International Mathematical Competition for students’ also called “Europe’09 student olympiad” which was held in Czech Republic, Ostrava. We also give some problems and one solution of not the hardest problem.
Keywords: olympiad; European; student’s